EFFECTIVE STRATEGIES FOR LEARNING ENGLISH AS A FOREIGN LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Learning English as a foreign language can be both challenging and rewarding. This article explores several effective strategies that help learners acquire English more efficiently. The study highlights the importance of motivation, consistent practice, the use of technology, and exposure to authentic materials. The findings suggest that combining traditional and modern techniques leads to successful language acquisition.